Enhancing Lecturer Performance: Investigating the Mediating Role of Organizational Citizenship Behavior - Fajar Supanto (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2023)
This paper investigates the role of organizational citizenship behavior as a mediator in the effect of organizational commitment, leadership style, and organizational culture on lecturer performance and the role of gender as a moderating variable. The number of research samples includes 294 lecturers from private and public universities in East Java, Indonesia. The data were analyzed using structural equation modeling (SEM) with AMOS version 24. The results showed that behavioral variables, including organizational commitment, leadership style, and organizational culture, mediated by organizational citizenship behavior, improved lecturer performance. The results obtained demonstrate that behavioral variables have a significant influence on lecturer performance. The results of this study also show that gender as a moderation variable is empirically proven to increase the influence of behavioral variables on lecturer performance. Our study proposes that behavioral variables are key components that contribute to lecturer performance in pursuing their passion and enhancing their performance.Keywords: Leadership Style, Lecturer Performance, Organizational Commitment, Organizational Culture